25 Good Reasons Why Beer is Better than Women and Other Qualities of the Female: Gender and the Non-Seriousness of Jokes - Greenhill, Pauline; Baldwin, Kjerstin; Blais, Michelle; Brooks, Angela; Rosbak, Kristen (Ethnologies, 1993)
Tellings of blonde jokes examined using a discourse analysis sensitive to power dynamics between women and men provide an illustration of patriarchal strategy which parallels that of the xerox-lore “25 Good Reasons Why Beer is Better Than Women”; the advocacy of mutual contradictions in which you must take this seriously, yet you must take this as a joke. Our discussion places discourse analysis in the service of feminist theory by showing how in cross sex joking interactions initiated by men and involving misogynist material like blonde jokes, a woman’s options for responding are limited and fundamentally unsatisfying. Some of the examples of blonde joke tellings show how women employ responsive counter-tactics, but analysis indicates why these strategies are problematic, compelling them to make choices between equally undesirable options, so limited that even making a choice is oppressive.